2020
DOI: 10.3389/fnins.2020.00494
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology: A Promising Approach for Delivery of Neuroprotective Drugs

Abstract: Central nervous system (CNS) disorders especially neurodegenerative disorders are the major challenge for public health and demand the great attention of researchers to protect people against them. In past few decades, different treatment strategies have been adopted, but their therapeutic efficacy are not enough and have only shown partial mitigation of symptoms. Blood-brain barrier (BBB) and blood-cerebrospinal fluid barrier (BSCFB) guard the CNS from harmful substances and pose as the major challenges in de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
88
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(104 citation statements)
references
References 257 publications
0
88
0
Order By: Relevance
“…They facilitate a more targeted and efficient brain delivery and reduce side effects at the same time [223]. The advantage of using nanotechnology-based drug delivery systems has been shown for different CNS indications, such as epilepsy, psychosis-related disorders and glioma [152,[223][224][225][226][227].…”
Section: Systemic and Cns Side Effectsmentioning
confidence: 99%
“…They facilitate a more targeted and efficient brain delivery and reduce side effects at the same time [223]. The advantage of using nanotechnology-based drug delivery systems has been shown for different CNS indications, such as epilepsy, psychosis-related disorders and glioma [152,[223][224][225][226][227].…”
Section: Systemic and Cns Side Effectsmentioning
confidence: 99%
“…Conversely, EVs can cross the BBB to affect the migration of immune cells, which, in turn, promotes disease progression in MS. For example, microglia, astrocytes, and platelets shed exosomes containing metalloproteinases and caspase-1 in response to stimulation by proinflammatory cytokines, such as TNF. It is well-known that these enzymes are able to induce BBB disruption and promote lymphocyte and myeloid cell migration into the CNS (48,49). Meanwhile, in MS patients, Barry et al, found that EVs released from activated T cells can promote monocyte recruitment and upregulate intercellular cell adhesion molecule-1 (ICAM-1) in endothelial cells as well as macrophage-1 antigen (Mac-1) expression in monocytes.…”
Section: Evs and Autoimmune Diseases Multiple Sclerosismentioning
confidence: 99%
“…These nano-sized systems have a remarkable aptitude for the targeted delivery of a specific drug dose to specific cells (such as cancer cells), without disturbing the physiology of the normal cells [ 9 ]. In addition, the targeted nano systems are able to ameliorate poor drug diffusion/release profiles, improve drug solubility, and boost bio-distribution and immunogenicity [ 10 ].…”
Section: Introductionmentioning
confidence: 99%